Oil-producing flowers of Sisyrinchium species (Iridaceae) and their pollinators in southern South America - Cocucci, Andrea Aristides (2001)
The floral relationships existing between the mainly New World genus Sisyrinchium (Iridaceae) and oil-collecting bees were investigated in southern South America. In addition to a single species known before as producing floral oil and being pollinated by oil-dependent bees, the present paper documents 11 further species of Sections Sisyrinchium and Echthronema (including Sect. Cephalanthum), which share this ecological status. The oil is secreted by one-celled, headed glandular trichomes which form in many species dense carpets (elaiophors) covering the staminal column basally, rarely parts of free filaments or tepals. Based on literature, 23 additional species possessing columnar hair carpets, presumable elaiophores, are listed. The principal and in some taxa exclusive visitors of oil-bearing S. are species of Lanthanomelissa (Anthophoridae-Tapinotaspidini), a southern genus that appears to have coevolved with its oil hosts. The females bear special scrapers on the forelegs by which they disrupt the oil-filled cuticular blisters of the hairs to forage the fluid. The oil then becomes mixed with pollen passively taken up from the same flower. Species of Tapinotaspis and Chalepogenus (Tapinotaspidini) also forage oil in S. species. The oil-harvesting and pollinating procedure is described in detail for S. arenarium, chilense, pachyrhizum, and laxum. Sympatric S. species may display divergent day-times of flower opening. - Altogether, seven flower types including taxa lacking elaiophors are discriminated in S. The latter - pollen flowers exploited by polylectic bees - are distributed over the genus and predominate in the related genera. The oil-based partnership of S. is so tar only known from the southern Neotropics, the probable centre of origin of both partners. The North America members of S., presumable derivatives from the Neotropical stock, bear vestigial elaiophors no longer used and are pollinated by pollen-collecting bees or are autogamous.